EPILOGUE: EVIDENCE FOR THE VALIDITY OF IMPLICIT APTITUDE AND THE NEED FOR CONSTRUCT VALIDATION. Issue 3 (July 2021) - DeKeyser, Robert; Li, Shaofeng
Abstract: In this commentary, we summarize the findings of the seven included studies that examined implicit language aptitude from various perspectives and highlight issues to be resolved in the validation of this new construct in second language research. We start by providing an overview of the contributions of the studies. We then identify the lack of convergent validity of the measures of implicit aptitude reported in the included studies and problematize the equally varied nature of the measurement of implicit knowledge—the outcome variable of aptitude research—and related concepts. In particular, by drawing on empirical evidence and theoretical claims, we attempt to clarify the relationships between implicit and explicit knowledge, implicit and explicit learning, and implicit and explicit instruction. Next, we draw attention to the interactions reported by the included studies between aptitude and outcome measures and between aptitude and instruction type, emphasizing the value and importance of interactional research. We conclude by making recommendations for future research.